the answer is 1/3(6x-9)=x-5
One solution was found :
x = -2
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
1/3*(6*x-9)-(x-5)=0
Step by step solution :
Step 1 :
1 Simplify — 3
Equation at the end of step 1 :
1 (— • (6x - 9)) - (x - 5) = 0 3
Step 2 :
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
6x - 9 = 3 • (2x - 3)
Equation at the end of step 3 :
(2x - 3) - (x - 5) = 0
Step 4 :
Equation at the end of step 4 :
x + 2 = 0
Step 5 :
Solving a Single Variable Equation :
5.1 Solve : x+2 = 0
Subtract 2 from both sides of the equation :
x = -2
One solution was found :
x = -2